2017
DOI: 10.17140/doj-4-133
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Fusion in Mandibular Primary Anterior Teeth: Report of a Rare Case With a Brief Review of Literature

Abstract: Fusion is a developmental anomaly of teeth. It is defined as the dentinal union of two embryologically developing teeth. It is more commonly seen in primary dentition and more frequently in incisor region. This paper reports a rare case which had the presence of bilaterally fused primary central incisor and lateral incisor in the mandibular region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“… 34 , 35 , 36 In reports of patients whose parents were consanguine, observed DDAs have included supernumerary teeth, oligodontia, mesiodens, fusion, dentin dysplasia, amelogenesis imperfecta, and talon cusp. 19 , 37 , 38 , 39 , 40 , 41 , 42 It has further been suggested that the higher variation of dental anomalies among individuals born from consanguineous marriages is due to an increase in homozygosity and a resulting loss of resistance to environmental stress. 43 …”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 , 36 In reports of patients whose parents were consanguine, observed DDAs have included supernumerary teeth, oligodontia, mesiodens, fusion, dentin dysplasia, amelogenesis imperfecta, and talon cusp. 19 , 37 , 38 , 39 , 40 , 41 , 42 It has further been suggested that the higher variation of dental anomalies among individuals born from consanguineous marriages is due to an increase in homozygosity and a resulting loss of resistance to environmental stress. 43 …”
Section: Discussionmentioning
confidence: 99%
“…This describes the concrescence between teeth #71 and #72 in this case. Bilateral involvement is rare and only recently reported by Mehta as a case with bilateral fusion of mandibular primary incisors, 28 whereas Shrivastava et al reported a single tooth fusion in the primary mandibular incisors. 29 In the presented case, teeth #71 and #72 revealed concrescence.…”
Section: Discussionmentioning
confidence: 99%